2018
DOI: 10.3892/ijo.2018.4545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-butenyl isothiocyanate on phenotypically different prostate cancer cells

Abstract: Isothiocyanates (ITCs) have gained increasing attention since they have been attributed the merits for the potential beneficial effects of cruciferous vegetable dietary consumption on cancer. The aim of the present study was to determine the cytotoxic effects of 3-butenyl ITC (3-BI) on prostate cancer (PC) cells under in vitro conditions. Two androgen-insensitive human PC cell lines, PC-3 and DU145, were assayed. Cells were cultured in the presence of increasing concentrations of 3-BI (5, 10, 30 and 50 µM) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Both compounds were tested (10 and 100 μM) following described protocols (MTT assays) using cisplatin as the control. 76,77 These experiments unequivocally confirmed that (±)-38 or (±)-47 do not exhibit a cytotoxic effect at the tested concentrations. The transwell migration assay 78 was used as a marker of A 2B AR antimetastatic activity.…”
Section: ■ Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Both compounds were tested (10 and 100 μM) following described protocols (MTT assays) using cisplatin as the control. 76,77 These experiments unequivocally confirmed that (±)-38 or (±)-47 do not exhibit a cytotoxic effect at the tested concentrations. The transwell migration assay 78 was used as a marker of A 2B AR antimetastatic activity.…”
Section: ■ Introductionsupporting
confidence: 61%
“…To rule out the potential cytotoxic effect of (±)- 38 or (±)- 47 in LNCaP, PC-3, and DU145, the cell growth inhibitory activity of these ligands was preliminarily evaluated. Both compounds were tested (10 and 100 μM) following described protocols (MTT assays) using cisplatin as the control. , These experiments unequivocally confirmed that (±)- 38 or (±)- 47 do not exhibit a cytotoxic effect at the tested concentrations. The transwell migration assay was used as a marker of A 2B AR antimetastatic activity.…”
Section: Resultsmentioning
confidence: 65%
“…Glucosinolate hydrolysis products are primarily responsible for the anticarcinogenic activity associated with consuming Brassica vegetables. These low-molecular weight compounds are able to rapidly diffuse into the cells of the intestinal epitheilium and modulate the expression of genes important to chemoprevention (e.g., those associated with xenobiotic metabolism, antioxidation, cell cycle regulation, apoptotic pathways, and stress response). Understanding the formation and disposition of glucosinolate hydrolysis products in the gut is key for understanding the bioactive potential of Brassica foods. In general, levels of glucosinolate hydrolysis products are lower in undamaged fresh Brassica as compared to Brassica with insect and/or physical damage as damage allows glucosinolates contact with myrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…The most attractive biological function of GSLs and their breakdown products is their anti-cancer activity (Sundaram et al 2021). The hydrolysis products of GSLs have been recognized to reduce the risk of various cancers, particularly ITCs that are reported to be potent anticarcinogenic compounds in lung, colorectal, breast, prostate, and other cancers both in vitro and in vivo (Gao et al 2018;Huang et al 2018;Lubecka et al 2018;Nú ñ ez-Iglesias et al 2018;Zhou et al 2019 (Myzak et al 2004), and diminished the formation of mammary tumors in rats exposed to 17b-estradiol (Palliyaguru et al 2020). Besides sulforaphane, other ITCs, including phenethyl ITC, benzyl ITC, allyl ITC, and indole-3-carbinol were also reported to inhibit cancer progression through multiple potential mechanisms, such as modulation of epigenome (Sundaram et al 2021).…”
Section: Gsl and Health Promotionmentioning
confidence: 99%